On H-property in bitopological spaces (Journal of Humanitarian and Applied Sciences, 2023)
In this paper, H-property is defined in bitopological spaces. Characterizations of spaces with H-property and the relationship between such spaces and P-T0, P-T1, P-T2 and P-regular spaces are discussed
Keywords: Axioms separated; H-property; bitopological spaces; P-regular space